2022
DOI: 10.3390/cancers14235791
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Treatment Patterns and Costs for Lung Cancer Have Not Resulted in Relevant Improvements in Survival: A Population-Based Observational Study in Catalonia

Abstract: Objective: Few published studies have described multidisciplinary therapeutic strategies for lung cancer. This study aims to describe the different approaches used for treating lung cancer in Catalonia in 2014 and 2018 and to assess the associated cost and impact on patient survival. Methods: A retrospective observational cohort study using data of patients with lung cancer from health care registries in Catalonia was carried out. We analyzed change in treatment patterns, costs and survival according to the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…This analysis reveals a noteworthy increase in survival in the latest period (2017-2021), coinciding with the introduction of immunotherapy as a treatment modality. In contrast, previous studies in our region did demonstrate similar survival differences after the implementation of immunotherapy, potentially attributed to the short follow-up time after treatment administration [23]. We did not observe a statistically significant increase in survival during the initial three periods analyzed (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This analysis reveals a noteworthy increase in survival in the latest period (2017-2021), coinciding with the introduction of immunotherapy as a treatment modality. In contrast, previous studies in our region did demonstrate similar survival differences after the implementation of immunotherapy, potentially attributed to the short follow-up time after treatment administration [23]. We did not observe a statistically significant increase in survival during the initial three periods analyzed (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016).…”
Section: Discussioncontrasting
confidence: 99%
“…In our region, only one previous study has been conducted to assess the cost of medical treatment and changes in survival among NSCLC patients based on data from tumor registries. This particular study observed an increase in treatment cost over a four-year period from 2014 to 2018 and did not show significant differences in survival rates [23].…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation